Perbedaan Pengaruh Latihan Penguatan Otot Kuadrisep terhadap Massa Bebas Lemak Ekstremitas Bawah dan Kekuatan Otot Kuadrisep pada Penderita Osteoartritis Lutut dengan Tingkat Aktivitas Fisik Rendah dan Tinggi - Susan Salsabila; Marina Annette Moeliono; Sunaryo Barki Sastradimadja; Dwi Agustian (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2018)
Introduction : More than in any other joint, osteoarthritis (OA) of the knee is a major cause of pain and disability. Quality of the lower limb muscles, whichis made up of lower extremity muscle mass and muscle strength of the quadriceps, is a risk factor for knee OA. Lower extremity fat-free mass (LE-FFM) represents lower extremity muscle mass. Physical activity level is a factor that affects LE-FFM and quadriceps muscle strength. Quadriceps muscle strengthening exercises can improve LE-FFM and quadriceps muscle strength. Methods : Forty two women with knee OA participated in this study. Interviews were conducted to obtain data about subjectscharacteristics, physical activity level and energy intake by recall 2 x 24 hours method. Measurement of LE-FFM used segmental multifrequency Bio-Impedance Analyzer (BIA) Tanita MC180 and quadriceps muscle strength used anisometric dynamometer BASELINE®. Evaluation was conducted before and after quadriceps muscle strengthening exercises [three times a week] for 8 weeks. Results : Quadriceps muscle strengthening exercises do not increase LE-FFM, but increasequadriceps muscle strength significantly (p=0,00) at a low level of physical activity also at high level physical activity. The difference of change in LE-FFM between the low level and high level physical activity is not different, but signific antly different for quadriceps muscle strength of the left extremity (p = 0.01) or right (p extremity= 0.04). Conclusion : LE-FFM changes between high and low physical activityis not different, whereas quadriceps muscle strength changes is different.